The strength of alpha and beta oscillations parametrically scale with the strength of an illusory auditory percept - Leske, Sabine; Tse, Ada; Oosterhof, Nikolaas N.; Hartmann, Thomas; Müller, Nadia; Keil, Julian; Weisz, Nathan (NeuroImage, 2014)
Studies investigating the role of oscillatory activity in sensory perception are primarily conducted in the visual domain, while the contribution of oscillatory activity to auditory perception is heavily understudied. The objective of the present study was to investigate macroscopic (EEG) oscillatory brain response patterns that contribute to an auditory (Zwicker tone, ZT) illusion. Three different analysis approaches were chosen: 1) a parametric variation of the ZT illusion intensity via three different notch widths of the ZT-inducing noise; 2) contrasts of high-versus-low-intensity ZT illusion trials, excluding physical stimuli differences; 3) a representational similarity analysis to relate source activity patterns to loudness ratings. Depending on the analysis approach, levels of alpha to beta activity (10-20. Hz) reflected illusion intensity, mainly defined by reduced power levels co-occurring with stronger percepts. Consistent across all analysis approaches, source level analysis implicated auditory cortices as main generators, providing evidence that the activity level in the alpha and beta range - at least in part - contributes to the strength of the illusory auditory percept. This study corroborates the notion that alpha to beta activity in the auditory cortex is linked to functionally similar states, as has been proposed for visual, somatosensory and motor regions. Furthermore, our study provides certain theoretical implications for pathological auditory conscious perception (tinnitus). © 2014 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Auditory illusion; Auditory perception; Gating-by-inhibition; Oscillatory activity; Similarity searchlight